Quality of life in cochlear implant users (Research, Society and Development, 2020)
Purpose: To evaluate the quality of life of cochlear implant users. Methods: Cross-sectional, observational and descriptive study, in which the World Health Organization Quality of Life-bref (WHOQOL-bref) questionnaire was applied to assess quality of life. The questionnaire assesses the physical, psychological, social relations and environment domains. Speech recognition was also assessed using an open set sentence test. The study included 25 cochlear implant users with at least one year of use, older than 18 years old, with a mean age of 46.79 years. For data analysis, the following statistical tests were used: Spearman's correlation, ANOVA test and T-Student test (p-value